Strategies of Food Safety Program Improvement to Prevent Food Poisioning Outbreak At Oil & Gas Industrial City - Kholil, Kholil; Sulistyadi, Kohar; Arlan, Subagja (ADI Publisher, 2019)
Nowadays, The food safety issue is a major problem which is related to the people’s health, livelihood, and the national economy. However, the food safety incidents occur frequently in recent years. These incidents bring the blow for the consumer’s confidence and it leads to the crisis of trust. These incidents not only affect the health and the safety of the consumers, but also affect seriously the health development of the food industry. Consumers require the higher requirement for the safety degree of the food. In order to reduce the occurrence of the food safety issue and ensure the quality of life, it is necessary to evaluate the food safety program implementation. Food safety program is importance barrier to prevent any food poisoning outbreak and issue in oil & gas industrial city. The purpose of this study is to determine the most priority and most important of food safety program in oil & gas industrial .Data analysis method used is descriptive analysis based on expert justification and assessed using SAST (Strategic Assumption Surfacing & Testing) and AHP (Analytic Hierarchy Process). The result of SAST analysis shows that program inspection and monitoring to food service facility (food producer) is most certain and most importance. Based on assessed by AHP analysis, the first priority of food safety program is also inspection & monitoring with a value 0.275, followed by food safety training (0.207), campaign & awareness (0.184), HACCP system (0.136), public involvement (0.108) and the last is law enforcement (0.090). The consistency value ratio (CR) is 0.01 less than 0.1.